2019
DOI: 10.14738/assrj.65.6389
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Job Satisfaction among Nurses in Public Health Facilities in Mombasa, Kwale and Kilifi Counties, Kenya

Abstract: The study sought to establish factors that influence job satisfaction of nurses in Kenya. This was necessitated by the need to contribute in bridging existing knowledge gap with regard to predictors of Nurses' job satisfaction. Whereas job satisfaction has been shown to influence nurse retention in employment, turnover rates and provision of quality patient care, job satisfaction of nurses has received minimal attention in Kenya. In Kenya, nurses who constitute the largest cadre of health care providers especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…According to our study, nurse job satisfaction is low in Ghana. We found that our results were almost similar to what we found among nurses in Ethiopia [81], Kenya [82] and Ghana [83]. In Ghana, however, job satisfaction among nurses has been studied extensively, but not concerning toxic leadership behaviour.…”
Section: Discussionsupporting
confidence: 88%
“…According to our study, nurse job satisfaction is low in Ghana. We found that our results were almost similar to what we found among nurses in Ethiopia [81], Kenya [82] and Ghana [83]. In Ghana, however, job satisfaction among nurses has been studied extensively, but not concerning toxic leadership behaviour.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, interpersonal relationship significantly affect job satisfaction. However, this is consistent with Yiltormanen (2021),Tengah et al (2019) revealed that nurse-nurse collaboration and relationship among nurses and other employees significantly affect nurses job satisfaction. Therefore, collaboration among professionals also increases job satisfaction.…”
supporting
confidence: 90%
“…There is evidence from earlier research that workplace social support, identified as support of supervisors and colleagues, has been acknowledged as a significant factor in alleviating negative consequences of occupational strain and stress (Brough and Pears, 2004;Schirmer and Lopez, 2001). Similarly, Tengah and Otieno (2019) found that lack of support leads to dissatisfaction and burnout among nurses in Kenya.…”
Section: Conceptual Modelmentioning
confidence: 99%